Powered Stretcher For Patient Transfer - Shea Wen, Lee (Universiti Sains Malaysia, 2022)
Patient lateral transfers between two adjacent surfaces could pose high musculoskeletal disorder risks for nurses and patient handlers. This dissertation presents the conceptual design of a mechanical system devoted to helping caregivers in handling and transferring bedridden patients. The chosen design comprises a conveyer belt and mecanum wheel system, which serve to retrieve and relocate the bedridden patient without causing discomfort and injuries. One of the objectives of this design is to reduce the number of medical personnel to only one and change their role from an active participant to that of an operational supervisor. A rough prototype was built with a functioning conveyer that could carry a 14 kg load. A simulation was also carried out to find the contact forces between the conveyer belt and dummy patient at varying inclination angles, speed, and belt material of the conveyer bed. The simulation results show that the least contact forces are experienced at an incline angle of 7-degree, conveyer speed of 0.05m/s and wool as belt material. There many limitations in the prototype design as this project represent the first step in developing and exploring viable design solutions and the list of components of a mechatronic system required in executing bedridden patient transport and repositioning.